Celebrating Third Anniversary of October Revolution in Altai Province in 1920 - K. A. Tishkina (Научный диалог)
This article examines the process of organizing celebratory events for the third anniversary of the October Revolution in the Altai Province. The focus is on the preparatory work, including the planning of festive activities, the coordination of themes for propaganda work, and the distribution of red fabric for making flags, among other things. The relevance of the study lies not only in the interest in the formation of the Soviet holiday calendar but also in the everyday life of the population in Siberia under the policy of ‘prodrazverstka’. By drawing on a wide range of sources, the article identifies the peculiarities of celebrating the third anniversary of the October Revolution, taking into account differences between urban and rural areas. It is determined that in cities, celebratory events were mass-oriented and covered all segments of the population, including parades, performances, and concerts. In rural areas, there were often no events due to weak propaganda work. Visiting individual graves and communal burial sites of those who died fighting for Soviet power became an important element of the holiday. The article concludes that celebrating the anniversary of the October Revolution in Siberia was a key aspect of the propaganda policy in favor of the Soviet state.